Practical Approach for DNA Extraction of Food Born Linguatula serrata Nymphs: an Analytical Method - Eslami, Gilda; Hajimohammadi, Bahador; Khalatbary, Sepideh; Zohortabar, Amin; Ardian, Mahmoud (Galen Medical Journal, 2014)
Background: Isolation of high quality genomic DNA is one of the most important steps in molecular biology studies related to food borne parasites. Usually, various protocols are used for different tissues but so far, there is no common, simple and cost benefit procedure for genomic DNA extraction of Linguatula serrata (L. serrata.) larvae as a Pentastomida endangering food safety. One of the procedures used in other studies is using commercial kits that are very expensive especially for developing countries which have this health problem. This study investigated a simple and cost-benefit method to extract genomic DNA form L. serrata. Materials and Methods: In this study, after collection of larvae from sheep, washing was done with phosphate buffer saline. The samples were grinded and incubated in lysis buffer at 56ÂºC overnight. The precipitation was done in absolute ethanol. Extracted DNA was analyzed using Agarose gel Electrophoresis and Spectrophotometery. Results: Results indicated that the mean concentration of extracted DNA was 59.3Â±2.84 ng/Î¼l, and the mean ratio of A(260)/ (280) was 1.6Â±0.3.Â It seems that the efficacy of this modified extraction method for L. serrata is appropriate. Conclusion: In conclusion, this simple, cost-effective, fast and easy to use method could replace inexpensive commercial kits in molecular laboratories for DNA extraction of Pentastomida and some other similar tissues. So, application of this analytical method could be useful to improve the safety of food especially liver and other meat products.